Cystogram use and outcomes in colorectal surgery involving bladder repair: a clinical audit. Issue 10 (14th November 2013) - Kwok, Chun Shing; Pal, Atanu; Sargen, Kevin
Abstract Background The role of routine cystograms after bladder repair during colorectal surgery is unclear so we aimed to evaluate this in our department. Methods We conducted a retrospective audit of colorectal surgical patients who had an operation and subsequent cystogram between 2006 and 2011 at the Norfolk and Norwich University Hospital. Data on patient characteristics, operative procedures and findings, and cystogram results were collected from electronic discharge summaries, operative notes and radiological records. Results A total of 59 operations were included and 92% had documented bladder involvement. The most common indications for surgery were diverticular disease (49%) and neoplastic disease (39%). Operations evaluated included high anterior resection, anterior resection, Hartmann's procedures and sigmoid colectomy. Although all patients had at least one post‐operative cystogram, only 46% of cases had instructions documented in the operative note for a cystogram to be arranged. Out of the 59 operations, 4 (7%) had cystograms that showed a leak. Repeat cystography in these cases showed no leak or smaller leak and no additional procedures were required. Two of the leaks occurred in cases that had extensive bladder involvement or bladder wall sepsis, and two occurred in cases where the operative findings revealed less major bladder pathology. Conclusions Our results suggest that majority of cystograms are negative. More studies are needed to evaluate if selective use of cystogram should be performed to reduce unnecessary the risks associated with radiation exposure and contrast exposure.